A cautionary note on the rank product statistic. Issue 11 (1st June 2016) - Koziol, James A.
Abstract : The rank product method introduced by Breitling R et al . [2004, FEBS Letters 573, 83–92] has rapidly generated popularity in practical settings, in particular, detecting differential expression of genes in microarray experiments. The purpose of this note is to point out a particular property of the rank product method, namely, its differential sensitivity to over‐ and underexpression. It turns out that overexpression is less likely to be detected than underexpression with the rank product statistic. We have conducted both empirical and exact power studies that demonstrate this phenomenon, and summarize these findings in this note. Abstract :